On the main constants in the probability theory - Mačys, Juozas Juvencijus (Lietuvos matematikos rinkinys, 2010)
We consider the place of the main mathematical constants in the probability theory. The present situation of their elementary theory is discussed.
Keywords: Euler–Mascheroni constant; number π; number e; irrationality; probability theory